2022
DOI: 10.3390/s22103918
|View full text |Cite
|
Sign up to set email alerts
|

Titanium and Silicon Dioxide-Coated Fabrics for Management and Tuning of Infrared Radiation

Abstract: Far infrared radiation (FIR) is emitted by every body at a given temperature, including the human body. FIR ranging between 4–14 μm is considered useful for cell growth, and the human body emits a maximum of infrared (IR) radiation at the wavelength of approximately 9.3 µm. In the present study, fabrics based on five different raw textiles having the same yarn count as well as the same weaving patterns were designed and created. Some of them were subjected to a coating process. The fabrics to be tested were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Textile coating allows modulation of IR by incorporating metallic materials, conductive powders, organic/inorganic materials and semi‐conductors 19,20 . Among those materials are zinc oxide, 21,22 antimony, 20 carbon nanotubes, 7 silver particles, 9,23–25 silica (SiO 2 ) particles, 19,26–35 titanium oxide (TiO 2 ), 27,28 and others 36,37 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Textile coating allows modulation of IR by incorporating metallic materials, conductive powders, organic/inorganic materials and semi‐conductors 19,20 . Among those materials are zinc oxide, 21,22 antimony, 20 carbon nanotubes, 7 silver particles, 9,23–25 silica (SiO 2 ) particles, 19,26–35 titanium oxide (TiO 2 ), 27,28 and others 36,37 …”
Section: Introductionmentioning
confidence: 99%
“…Assaf et al showed that 5% of sub‐metric SiO 2 particles inserted within PE membranes offer an efficient absorption of more than 35% of the infrared radiation between 5 and 15 μm of the nanocomposite, as compared to the neat membrane 26 . The coating of cotton, wool, viscose, acrylic, and cotton/polyester fabrics with different ceramic powder coatings such as SiO 2 for IR emissivity tuning and management has been studied by Yuce et al 28 demonstrating the efficient change of IR absorbance in the investigated wavelength range (8–14 μm). Likewise, Panwar et al 29 deposited Janus TiO 2 ‐SiO 2 particles on a cotton fabric surface and observed a clear NIR reflection due to the coupling of the high refractive index of TiO 2 to the large size of SiO 2 particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure1(a) shows the ATR-FTIR spectra of Am-Cot and the Am-Cot-CuO + TiO 2 samples. The spectrum of Am-Cot (Fig.1) shows a strong peak at 3000 cm − 1 assigned to hydroxyl (OH) groups stretching for intermolecular bonding of hydrogen bonds in cellulose, lignin and water(Yuce et al, 2022). The peak at 2907 cm − 1 is due to the stretching vibration of C-H present in cellulose and(Agrawal et al, 2019), and the band at 1628 cm − 1 is due to water present in the bres(Cheng et al, 2018).…”
mentioning
confidence: 99%
“…), is more feasible. [11][12][13] In recent years, researchers have successively proposed a variety of conventional statically tunable thermal emitters to achieve the goal of infrared properties modulation, which has the advantages of simple preparation and low cost. [14][15][16] Unfortunately, the structural parameters, material parameters, and arrangements of these structures are usually fixed after fabrication.…”
mentioning
confidence: 99%